Meningkatkan Mutu Evaluasi Pembelajaran: Analisis Soal Pilihan Ganda Bahasa Arab - Nuraisyah, Andini (STIQ Amuntai, 2024)
Learning evaluation is one part of the learning process. Through evaluation, a teacher can find out students' abilities and understanding of the material they have studied. Evaluation instruments require quality tests or questions in terms of validity, reliability, level of difficulty, distinguishing power and effectiveness of distractors. Question items prepared by a teacher to test students' abilities must be recommended to be tested for suitability based on these aspects so that the instruments that have been prepared can be used according to their function. This research was conducted using a descriptive methodology and quantitative research form. The research instrument used was 15 grade 5 PAS Arabic multiple choice questions and the research subjects were 5th grade students at SDIT Al Inayah for the 2023-2024 academic year who were tested by 37 participants. The results of the analysis of the questions in this study in the validity aspect were still not good because only 3 questions (20%) were valid. Then, in terms of the level of difficulty, it is sufficient but not yet balanced because no difficult questions were found. From the aspect of discriminating power, the questions studied were quite good and produced a discriminating power of each question which was 40% and good, reaching 33%. The effectiveness of the distractors in this study was also sufficient because 25% of the distractors were found to be functional, and 25% were rejected. Thus, from the results of this analysis, a teacher can improve and develop question items that are still not good in some of these aspects.